2010
DOI: 10.5012/bkcs.2010.31.02.291
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Gold Nanoisland Arrays from Layer-by-Layer Assembled Nanoparticle Multilayer Films

Abstract: This article introduces a facile nanoparticle self-assembly/annealing method for the preparation of nanoisland films. First, nanoparticle-polymer multilayer films are prepared with layer-by-layer assembly. Nanoparticle multilayer films are then annealed at ~ 500 o C in air to evaporate organic matters from the films. During the annealing process, the nanoparticles on the solid surface undergo nucleation and coalescence, resulting in the formation of nanostructured gold island arrays. By controlling the overall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…29,30 The nanoisland films prepared at 525 °C showed similar changes but with less extent (Δλ max = ~25 nm). The change was quite small but still clearly visible for the films generated at 550 °C (Δλ max = ~10 nm).…”
Section: Resultsmentioning
confidence: 88%
See 4 more Smart Citations
“…29,30 The nanoisland films prepared at 525 °C showed similar changes but with less extent (Δλ max = ~25 nm). The change was quite small but still clearly visible for the films generated at 550 °C (Δλ max = ~10 nm).…”
Section: Resultsmentioning
confidence: 88%
“…27,28 We have shown that the gold nanoisland arrays with various grain density and different average sizes could be obtained by controlling the overall thickness (number of layers) of nanoparticle multilayer films. 29 Gold nanoisland films obtained from the nanoparticle 2-layer films were quite polydisperse. Nanoisland films generated from the nanoparticle 8-layer films contained grains with higher density compared to the island films generated from the nanoparticle 5-layer films.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations